Cytotoxic and apoptotic effects of six herbal plants against the human hepatocarcinoma (HepG2) cell line - Nonpunya Apiyada; Sripanidkulchai Bungorn; Barusrux Sahapat; Weerapreeyakul Natthida; Machana Sasipawan; Thitimetharoch Thaweesak (BMC, 2011)
Abstract Background Six plants from Thailand were evaluated for their cytotoxicity and apoptosis induction in human hepatocarcinoma (HepG2) as compared to normal African green monkey kidney epithelial cell lines. Methods Ethanol-water crude extracts of the six plants were tested with neutral red assay for their cytotoxicity after 24 hours of exposure to the cells. Apoptotic induction was tested in the HepG2 cells with diamidino-2-phenylindole staining. DNA fragmentation, indicative of apoptosis, was analyzed with agarose gel electrophoresis. Alkylation, indicative of DNA damage, was also evaluated in vitro by 4-(4'-nitrobenzyl) pyridine assay. Results The extract of Pinus kesiya showed the highest selectivity (selectivity index = 9.6) and potent cytotoxicity in the HepG2 cell line, with an IC50 value of 52.0 ± 5.8 μg/ml (mean ± standard deviation). Extract of Catimbium speciosum exerted cytotoxicity with an IC50 value of 55.7 ± 8.1 μg/ml. Crude extracts from Glochidion daltonii, Cladogynos orientalis, Acorus tatarinowii and Amomum villosum exhibited cytotoxicity with IC50 values ranging 100-500 μg/ml. All crude extracts showed different alkylating abilities in vitro. Extracts of P. kesiya, C. speciosum and C. orientalis caused nuclei morphological changes and DNA laddering. Conclusion The extracts of C. speciosum, C. orientalis and P. kesiya induced apoptosis. Among the three plants, P. kesiya possessed the most robust anticancer activity, with specific selectivity against HepG2 cells.